Zooplankton rhapsody: Unexpected response in community following increased fish predation - Estlander, S.; Horppila, J.; Olin, M.; Nurminen, L.; Rask, M.; Lehtonen, H. (Boreal Environment Research Publishing Board, 2024)
The impact of increased fish density on the crustacean zooplankton was studied in a small, forest lake. Interestingly and contrary to our hypothesis, increased fish density resulted in an increase in biomass of large-sized cladocerans, but a decrease in biomass of smaller and dominant cladoceran species. Thus, the effect of increased planktivory of fish was likely tempered by compensatory dynamics of zooplankton, wherein abundance of some species increased to compensate for population decreases by other species. This change in the relative species composition of zooplankton was seen as the increased diversity in crustacean zooplankton community. We conclude that instead of simple “top-down” or “bottom-up” regulation of zooplankton, the diverse array of connections among species is more likely to cause community dynamic fluctuations in zooplankton. Moreover, behavioural changes e.g. habitat change of fish may also have a pronounced effect on the response of zooplankton community on fishing.